The neural plasticity and efficacy of acupuncture for post-stroke dysphagia: protocol for a randomized controlled trial with fMRI and DTI - Wei Liu; Wenyi Ge; Qi Zhao; Xiaonong Fan; Yibing Li; Hongbo Jia; Kangchen Lei; Songjiao Li; Li Li; Yuzheng Du; Jian Liu; Yan Shen; et al. (BMC, 2024)
Abstract Background Dysphagia, a common complication of acute stroke, is associated with increased mortality and morbidity. Acupuncture, a widely used swallowing therapy in China, has been suggested as an effective therapy for treating Post-Stroke Dysphagia (PSD) by recent meta-analyses and guidelines. The use of resting-state functional Magnetic Resonance Imaging (rs-fMRI) and Diffusion Tensor Imaging (DTI) could explore the change of regional spontaneous neural activity, functional relationships between brain regions, and white matter connectivity patterns after acupuncture intervention for PSD. This trial aims to evaluate the efficacy of acupuncture treatment for PSD and explore its central mechanism by neuroimaging. Methods/design This randomized controlled trial will recruit 40 PSD patients. All patients will be randomized to either the Real Acupuncture (RA) or Sham Acupuncture (SA) group by a ratio of 1:1. All patients will receive immediate acupuncture treatment in the MRI scanning room, followed by four weeks of long-term acupuncture treatment. The primary outcomes are the rs-fMRI and DTI indicators, which will be evaluated after the immediate and long-term acupuncture treatment. The secondary outcomes are the scales that assess the efficacy, including the Functional Oral Intake Scale (FOIS), Water Swallowing Test (WST), Swallowing Quality Of Life Questionnaire (SWAL-QOL), and National Institute of Health Stroke Scale (NIHSS). The modified version of the Massachusetts General Hospital Acupuncture Sensation Scale (M-MASS) and fMRI sensation record table will also be evaluated. Discussion This protocol presents the design of a randomized, single-blind trial that will evaluate the efficacy and explore the neural plasticity of acupuncture treatment for PSD. This trial will deepen our insight into the clinical value of acupuncture for PSD and initially probe into the time-dosage-effect mechanism of acupuncture. Trial registration numbers Chinese Clinical Trial Registry ( www.chictr.org.cn ) ChiCTR2300067480. This study was registered on 9th January 2023.